Spatial Information Theory 12th International Conference, COSIT 2015, Santa Fe, NM, USA, October 12-16, 2015, Proceedings - Fabrikant, Sara Irina; Raubal, Martin; Bertolotto, Michela; Davies, Clare; Freundschuh, Scott; Bell, Scott (Theoretical Computer Science and General Issues, 2015)
This book constitutes the proceedings of the 12th International Conference on Spatial Information Theory, COSIT 2015, held in Santa Fee, NM, USA, in October 2015. The 22 papers presented in this book were carefully reviewed and selected from 52 full paper submissions. The following topics are addressed: formalizing and modeling space-time, qualitative spatio-temporal reasoning and representation, language and space, signs, images, maps, and other representations of space, navigations by humans and machines.